Management Means Infrastructure in Elementary School State 1 Bitung - Rawis, Joulanda A.M.; Tambingon, Henny Nikolin; Lengkong , Jeffry Sony Junus; Dondokambey, Robby; Dotulong, Reza A. W.; Ratumbuisang, Keith F; Rambitan, Maya C. (International Journal of Information Technology and Education, 2024)
Currently, one of the factors that determines the quality of education in Indonesia is facilities and infrastructure. Educational facilities and infrastructure can help students learn more comfortably. This Study aims to describe management means and infrastructure in School Base (SD) Country 1 Bitung, constraints faced, and solutions for overcoming these obstacles. This research uses a qualitative approach. The collection of data is done with interviews, observations, and documentation. Respondents to this research are head school, Teacher, And staff system business. Results study show that Procurement of facilities and infrastructure prioritizes sanitation development. Facilities management infrastructure Which covers planning, procurement, use, maintenance, and deletion means infrastructure has walked with Good. Constraints faced are the lack of funds needed for the procurement process and the lack of administrative staff in management process management means and infrastructure.